Controlled Switching of the Number of Skyrmions in a Magnetic Nanodot by Electric Fields (Adv. Mater. 11/2022). Issue 11 (17th March 2022) - Hou, Zhipeng; Wang, Yadong; Lan, Xiaoming; Li, Sai; Wan, Xuejin; Meng, Fei; Hu, Yangfan; Fan, Zhen; Feng, Chun; Qin, Minghui; Zeng, Min; Zhang, Xichao; et al.
Abstract : Skyrmion Clusters An electric‐field‐driven cascading transition of skyrmion clusters in a nanostructured ferromagnetic/ferroelectric multiferroic heterostructure is realized by Zhipeng Hou, Yangfan Hu, and co‐workers, as described in article number 2107908, allowing a continuous multilevel transition of the number of skyrmions in a one‐by‐one manner. Most notably, the transition is nonvolatile and reversible. These results open up a new direction for constructing low‐power‐consuming, nonvolatile, and multibit skyrmionic devices.